Minimally Invasive Surgical Approach for the Treatment of Miller’s Class I Recession Defects- A Report of Two Cases - Ridhima Uppal; Anurag Bhatnagar; Amit Bhardwaj; Aishaan Sharma; Madhur Goyal (Journal of Clinical and Diagnostic Research, 2022)
Gingival recession is defined as the apical displacement of the gingival margin leading to exposure of the root surface. Occurrence of the gingival recessions in the anterior teeth is a major concern for the patients as it leads to compromised aesthetics and achieving the aesthetics and functional requirements of the patients remains a major therapeutic challenge for the treating dental surgeon. Incorporating the principles of Minimally Invasive Surgical Technique (MIST), surgical trauma is minimised, thus causing less cell damage, eventually resulting in less inflammation and less discomfort. MIST aims to achieve aesthetically superior outcomes that are made possible due to improved visual acuity. Therefore, the intent of this case report was to emphasise the impact of implementing the minimally invasive surgical procedure in the management of marginal gingival recessions using the conventional Coronally Advanced Flap (CAF) and the Tarnow’s technique, with the use of microsurgical instruments and magnifying surgical loupes.